VD_FINDINFO HC / 2024 / 709 vom 23. August 2023 - VD Tribunal cantonal (2023)
BAIL À LOYER, RÉSILIATION ABUSIVE, ANNULABILITÉ, PROLONGATION DU BAIL À LOYER, MOTIF | 257f al. 3 CO, 271 al. 1 CO, 272 al. 1 CO, 272 al. 2 CO, 272a CO